Torture, confession and death penalty: a tragic case of juvenile sexual violence decided by the Rota of Lucca in the XVI century (Italian Review of Legal History, 2019)
This paper deals with the study of a late 16th century decisio by the Rota of Lucca, one of the major courts established in modern times in Italy and Europe. The author was Giuseppe Ludovisi, judge and jurist from Assisi, who during his career held important positions, including that of auditor of the Rota of Perugia, Lucca and Florence. The collections of his Perugian and Lucchese decisiones were published respectively, in 1572 and 1577. His Conclusiones communes (1581) and the Receptae sententiae (1584) also went to print. The seventeenth of his decisiones in Lucca concern a tragic case of sexual violence followed by death, made even more dramatic by the age of the accused - a boy of fifteen - and above all the victim - a child of only two years of age.  With numerous doctrinal, advisory and normative citations and judicial precedent, the ruling dealt with two important issues in the context of juvenile criminal justice of the time.  The first related to the validity of the confession extracted following torture of a child without the assistance of a curator.  The second concerned the penalty to be imposed and, in particular, the imposition of the death penalty on a pubescent minor. A fifteen-year-old boy was accused of raping his two-year-old granddaughter, who later died as a result of injuries sustained in her private parts.  On the basis of evidence of guilt the judge had ordered that the young man be subjected to torture.  As a result of said "torments" the adolescent had confessed not only to have raped the girl several times, but also to other illicit behaviors (the rape of another six-year-old girl, sexual intercourse of various kinds, including sodomy).Ludovisi attested that according to the ius commune the appointment of a curator  in favor of the minor would have been necessary, as established by an imperial constitution. Nevertheless,  Ludovisi ultimately accepted the validity of the confession on the basis of a consuetudo, though contra legem, followed in practice and also in many doctrinal opinions.  This conclusion must have been reached by also taking into account the assistance, in the trial, of two representatives of the Senate of Lucca, whose presence was equivalent to that of the princeps, which de jure substitutes for any necessary requirement. Because of the punishment of the adolescent, his imputability was taken for granted as a pubescent minor and therefore as a doli capax.  In theory, in light of his age, the boy would still have been worthy of a reduction of sentence by arbitrary decision of the judge, without prejudice to the cases of extremely willful atrocissimi crimes, for which the death penalty could be imposed. However, the judge indicated that the nature and extent of the sanction had to be assessed in light of the statute of the city of Lucca, which regulated the punishment of minors under eighteen years of age.  In such cases, in fact, if a minor was accused of a crimen for which a corporal punishment was envisaged, a judge could still issue a sentence for a milder sanction, considering the personal condition, age and obviously the qualitas facti. However, the most favorable treatment could not have taken place for the crimes laese maiestatis, of machination against the peace and freedom of the city of Lucca and of willful murder. In particular, then, according to the judge from Assisi, other criminal hypotheses in quibus est eadem et maior ratio were to be assimilated to this latter criminal offense. In this regard, Ludovisi asserted that for the crimes in question the reckoning of the eadem ratio of willful homicide seemed to occur, indeed a major ratio concerning the severity of the sentence and the other confessed crimes. On these assumptions, the application of the statute rule of Lucca concerning willful murder seemed unavoidable. But, as for the question relating to confession, the reasoning of the rotal judge was reversed: capital punishment, foreseen for  willful murder, should not and could not be imposed on the boy precisely on the basis of the legislation in force in Lucca. According to the magistrate, contrary to appearance, in reality the eadem ratio lacked in substance, as there was no subjective element of willful murder. In fact, despite the rape being followed by the death of the child, the accused young man had acted not animo occidendi but explendi libidinem. Moreover, even apart from the case of the Lucca statutum, the doctrine and the practice had been attested for some time on a rather clear position: willful murder, as to the imposition of the death penalty, could not be equated to  negligent murder, not even  in case of lata culpa. Following the decisio, the Umbrian magistrate and jurist also dwelt on the position, supported by authoritative doctrine, according to which the death penalty could not be imposed on a minor, not even for very serious offences committed. In this regard, Ludovisi listed a vast number of cases but, despite this, he defined this opinion as falsissima and groundless. The rota magistrate, ultimately, stated that for minors over fourteen the judge had an arbitrium that would allow him to mitigate the ordinary penalty but also to inflict the death sentence. In conclusion, Ludovisi considered that he should nevertheless comply with the ius proprium, that is to say the Lucca statutes. And since these expressly forbade the imposition of capital punishment on children under the age of eighteen, except for the commission of the aforementioned three kinds of crimes, of which, however, the boy was not charged, the adolescent’s life was spared. The learned, justified and to some extent original decisio of Ludovisi - from which the close connection between legislation, science and practice in the ius commune system emerges once again - was not denied by the operative provisions of the judgement. The teenager avoided the death penalty but received an extremely severe sentence: four years in prison and, above all, the destination ad triremes perpetuas. Even the boy's family did not emerge unscathed from the trial, as his father was sentenced to pay a sum of two thousand crowns to the Hospital of the Misericordia of Lucca. Thus concluded a judicial case both disturbing and tragic - for the very small victim, for the very young author of the crime and certainly also for their respective families. In regards to the case, beyond any consideration of the merits of the sentence, the judge and jurist Giuseppe Ludovisi showed in full his technical competence as well as all his commitment to his duties as a representative of legal institutions. The theme of the imputability of minors and of their judicial and punitive treatment in general is certainly engaging in its complexity and delicacy, whatever the approach, scientific or otherwise, one intends to dedicate to it.  For the historian of law, it certainly represents a field still worthy of research and exploration in legal science, in legislation and above all in judicial practice. Here investigation can be made of the transformations and social dynamics on which depends the degree of civility of the punishment  of those human beings not yet fully mature.
Keywords: torture; death penalty; confession; XVI century; juvenile delinquency; sexual abuse